A review on the potential effects of tsunami on built environment. (2020) - Rose Enid Teresa, A.; Jerry Vasanth, G.D.N.; Vidya, C.
Abstract: Over the past two decades, natural calamities like tsunamis and earthquakes occur more frequently, posing a serious threat to the human race. About 80% of these calamities have the "Ring of Fire" in the Pacific Ocean as its epicenter, causing extreme destructions due to the huge amount of energy and moving water bodies striking the adjoining land masses. Tsunamis cause heavy damage to human lives killing almost 430, 000 lives since 1850, as it is almost impossible to flee from the mammoth waves. Huge waves collapse concrete buildings causing electrocution, explosion of gas plants, breakage of tanks and industries due to the floating debris that comes along with the killer waves. Following a tsunami, loss of infrastructures and economies is inevitable. This paper highlights the types of tsunamis and their potential effects on built structures and explains the association between tsunami related injuries and household level risk factors, including damages to built environment. Earlier studies have revealed that women, children and elderly citizens are at greater risk, and proximity to sea shores increase their risk of being affected. This finding, together with the risk of living in permanent structures in tsunami threatened areas should be an eye opener for the policy makers.